AN ANALYSIS OF AMERICAN SLANGS AND IDIOM USED IN THE SHAWSHANK REDEMPTION MOVIE - Utama, Nofra; Erni, Erni; Syarfi, M (TELL - US JOURNAL, 2024)
This study aims to identify and interpret various forms of slang and idioms that appear in film dialogue, as well as analyze their function and meaning in narrative and social contexts. The methodology used in this research is qualitative analysis with a descriptive approach. Dialogue in films is analyzed to identify examples of slang and idioms, which are then categorized by type, such as binomials, idiomatic phrases with verbs, and similes. In addition, the context of use of each expression is analyzed to understand how they contribute to the characterization and development of the plot. The research results show that the use of slang and idioms in "The Shawshank Redemption" not only enriches the dialogue and provides authenticity to the characters, but also reflects the social dynamics and hierarchy in the prison environment. Slang is used as a tool of secret communication between prisoners, while idioms help express the characters' emotions and experiences in a more lively and expressive way. In conclusion, this analysis reveals that the slang and idioms in "The Shawshank Redemption" have an important role in shaping the narrative and deepening the audience's understanding of the characters and their social context. This research contributes to the study of language in film media and enriches understanding of informal language use in certain cultural contexts.